Teaching and Learning with Technology: Ramification of ICT Integration in Mathematics Education - Marvelino M. Niem; Rizza U. Veriña; Emil C. Alcantara (Southeast Asian Mathematics Education Journal, 2020)
The study was undertaken to determine the extent of integration of Information and Communication Technology (ICT) to mathematics teaching and learning processes among junior and senior high school Mathematics teachers in the Division of Tanauan City. Further, the research also identified challenges encountered in ICT-based teaching and learning mathematics. This study employed mixed method of research, survey questionnaire, interview, and focus group discussion(FGD)with the 77teachers. The respondents were determined using Raosoft at five percent margin of error and used stratified random sampling. The frequency, percentage, mean, standard deviation, and T-test were the statistical tools used to analyse the data. Based on the findings, majority of the respondents were female, bachelor’s graduate, from teachers I to III, 15 years below in the service and not active in attending ICT-related seminars. Most of them use technology in writing lesson plans, in computing students’ results and, in teaching the lesson through power point presentations. However, due to the lack of resources and little fund from the Maintenance and Other Operating Expenses (MOOE), the respondents rarely use telecommunication devices such as cable, satellite, fax-machine, etc. to interact with students. There is a significant difference between the extent of the use of ICT in teaching and learning mathematics and years in teaching. Lack of ICT facilities and trainings attended and confidence in the use of ICT were the commonly identified challenges. With the aforementioned, the researchers recommended that mathematics teachers must be given more opportunities to participate ICT-based seminars and trainings.